2021
DOI: 10.1016/j.ajic.2021.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Intention to COVID-19 vaccination and associated factors among health care workers: A systematic review and meta-analysis of cross-sectional studies

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
125
5
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(151 citation statements)
references
References 41 publications
18
125
5
3
Order By: Relevance
“…A recent meta-analysis on vaccine hesitancy among health workers (HCWs) showed that male participants were more likely to receive the COVID-19 vaccine compared to females when it was available. The previous study suggested that this phenomenon could be because of the reported higher mortality rates among males due to COVID-19 [52].…”
Section: Discussionmentioning
confidence: 96%
“…A recent meta-analysis on vaccine hesitancy among health workers (HCWs) showed that male participants were more likely to receive the COVID-19 vaccine compared to females when it was available. The previous study suggested that this phenomenon could be because of the reported higher mortality rates among males due to COVID-19 [52].…”
Section: Discussionmentioning
confidence: 96%
“…Studies examining the acceptance of the COVID-19 vaccine among healthcare providers, students in health-related fields, and the general public showed that demographic factors of age, gender, and education were significantly associated with intention to use the vaccine [12]. In addition, individual perceptions regarding perceived infection risk, infection severity, and perceived vaccine risks and benefits are suggested predictors of vaccine acceptance and hesitancy [11,[15][16][17][18]. To our knowledge, this is the first study to report the vaccine acceptance rate and identify attitude and belief factors that underpin vaccination intentions among health science students in Morocco prior to the start of the national COVID-19 vaccination campaign.…”
Section: Introductionmentioning
confidence: 99%
“…3 One of the earliest reviews of 24,952 HCWs (data till February 2021) estimated that COVID-19 vaccination willingness of HCWs worldwide was a mere 51%. 4 The vast majority of these HCWs’ studies have focused on physicians, nurses, or medical students leaving a knowledge gap on COVID-19 vaccination preferences of several other groups of HCWs. 3 , 4 , 5 , 6 …”
mentioning
confidence: 99%
“… 4 The vast majority of these HCWs’ studies have focused on physicians, nurses, or medical students leaving a knowledge gap on COVID-19 vaccination preferences of several other groups of HCWs. 3 , 4 , 5 , 6 …”
mentioning
confidence: 99%